Effect of silicon on activity coefficients of siderophile elements (Au, Pd, Pt, P, Ga, Cu, Zn, and Pb) in liquid Fe: Roles of core formation, late sulfide matte, and late veneer in shaping terrestrial mantle geochemistry. (1st July 2018) - Righter, K.; Pando, K.; Humayun, M.; Waeselmann, N.; Yang, S.; Boujibar, A.; Danielson, L.R.
Abstract: Earth's core contains ∼10% of a light element that may be a combination of Si, S, C, O or H, with Si potentially being the major light element. Metal-silicate partitioning of siderophile elements can place important constraints on the P-T-fO2 and composition of the early Earth, but the effect of Si alloyed in Fe liquids is unknown for many of these elements. In particular, the effect of Si on the partitioning of highly siderophile elements (Au, Re and PGE) is virtually unknown. To address this gap in understanding, we have undertaken a systematic study of the highly siderophile elements Au, Pd, and Pt, and the volatile siderophile elements P, Ga, Cu, Zn, and Pb at variable Si content of metal, and 1600 °C and 1 GPa. From our experiments we derive epsilon interaction parameters between these elements and Si in Fe metallic liquids. The new parameters are used to update an activity model for trace siderophile elements in Fe alloys; Si causes large variation in the magnitude of activity coefficients of these elements in FeSi liquids. Because the interaction parameters are all positive, Si causes a decrease in their metal/silicate partition coefficients. We combine these new activity results with experimental studies of Au, Pd, Pt, P, Ga, Cu, Zn and Pb, to derive predictive expressions for metal/silicate partition coefficients which can then be applied to Earth. The expressions are applied to two scenarios for continuous accretion of Earth; specifically for constant and increasing fO2 during accretion. The results indicate that mantle concentrations of P, Ga, Cu, Zn, and Pb can be explained by metal-silicate equilibrium during accretion of the Earth where Earth's early magma ocean deepens to pressures of 40–60 GPa. Au, Pd, and Pt, on the other hand become too high in the mantle in such a scenario, and require a later removal mechanism, rather than an addition as traditionally argued. A late reduction event that removes 0.5% metal from a shallow magma ocean can lower the Au, Pd, and Pt contents to values near the current day BSE. On the other hand, removal of 0.2–1.0% of a late sulfide-rich matte to the core would lower the Au, Pd, and Pt concentrations in the mantle, but not to chondritic relative concentrations observed in the BSE. If sulfide matte is called upon to remove HSEs, they must be later added via a late veneer to re-establish the high and chondritic relative PUM concentrations. These results suggest that although accretion and core formation (involving a Si, S, and C-bearing metallic liquid) were the primary processes establishing many of Earth's mantle volatile elements and HSE, a secondary removal process is required to establish HSEs at their current and near-chondritic relative BSE levels. Mn and P - two siderophile elements that are central to biochemical processes (photosynthesis and triphosphates, respectively) - have significant and opposite interactions with FeSi liquids, and their mantle concentrations would be notably different if Earth had a Si-free core.